Flow Cytometry-Based Protocols for the Analysis of Human Plasma Cell Differentiation - Khoenkhoen, Sharesta; Ádori, Monika; Pedersen, Gabriel K.; Karlsson Hedestam, Gunilla B. (Frontiers in Immunology, 2020)
Humoral immunity is established after differentiation of antigen-specific B cells into plasma cells (PCs) that produce antibodies of relevant specificities. Defects in the development, activation, or differentiation of B cells severely compromises the immune response. Primary immunodeficiencies are often characterized by hypogammaglobulinemia and the inability to mount effective antigen-specific antibody responses, resulting in increased susceptibility to infections. Common variable immunodeficiency (CVID) is the most prevalent primary immunodeficiency, but in most cases the underlying genetic causes are unknown or their roles in disease pathogenesis are poorly understood. In this study, we developed a protocol for in vitro stimulation of primary human B cells for subsequent analyses of PC differentiation and antibody production. With this approach, we were able to detect a population of CD38+ IRF4+ Blimp-1+ cells committed to PC fate and IgG production, including when starting from cryopreserved samples. The application of functional assays to characterize PC differentiation and possible defects therein in B cells from CVID patients could increase our understanding of the disease pathophysiology and underlying mechanisms.